Social and market acceptance of photovoltaic panels and heat pumps in Europe: A literature review and survey. (March 2022) - Peñaloza, Diego; Mata, Érika; Fransson, Nathalie; Fridén, Håkan; Samperio, Álvaro; Quijano, Ana; Cuneo, Alessandra
Abstract: This paper examines the main non-technical factors that influence social and market acceptance of solar photovoltaic panels and heat pumps in buildings. The paper discusses results from a literature review and a survey of European stakeholders. Statistical analysis results of survey data identify the most common barriers to adoption of renewables as: limited information about the technology, financial concerns, and sociodemographic factors. Survey results indicate variability in market and social acceptance of renewables between stakeholders and countries. The investment cost of the technologies is identified as a barrier to adoption for all countries. Legal and organizational issues are identified as barriers in Spain. Economic and legal barriers are identified as barriers in Latvia and Belgium. The respondents from Germany only identify investment cost as a barrier. Economic aspects are identified as the main barriers among public building owners and the general public. Businesspeople identified the largest number of barriers, including economic aspects, lack of information, trust, business models, and legal issues, while private building owners identified the least number of barriers, with concerns only related to economic aspects. Results of this study provide valuable information for policymaking focused on increasing the adoption of renewables in the building sector. Additionally, this study identifies the need to increase environmental awareness among citizens and increase the availability of information about technologies to stakeholders. Citizens should be informed about the recoupment of the investment costs of the technologies to offset the perception of high investment costs, long payback time, and lack of proper business models. Highlights: A literature review of social and market acceptance of renewable energy technologies. Review based on a conceptualization of acceptance. A stakeholder survey based on key aspects of acceptance identified in the review. Statistical data analysis to identify trends and correlations. Results can validate previous findings or create new knowledge for decision makers.